Analisis Pengaruh Manajemen Laba Terhadap Nilai Perusahaan dengan Good Corporate Governance Sebagai Variabel Moderasi (Studi Kasus Pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2015-2017) - Theresia Shirley Tanadi dan Indra Widjaja (Universitas Tarumanagara, 2019)
The main objective of this research is to collect the empirical evidence of the influence of earnings management to the Firms’ value, with good corporate governance as the moderating variable, for Manufacturing Firms that are registered to the Indonesian Stock Exchange as of 2015 – 2017. Manufacturing Firms as the research subject, with Consumer Goods Industry and Basic Industry & Chemical sector. The research variables are (1) profit management, with proxy discretionary accruals modified jones; (2) Firm’s value, with proxy price to book value; and (3) good corporate governance, with proxy independent commissioner proportion and audit committee. This research used simple and moderated regression analysis method. The result indicates that earnings management has an impact on the Firms’ value and audit committee moderates the influence of earnings management to Firms’ value, whereas independent commissioner does not.